PENGARUH UKURAN KAP, FEE AUDIT, DAN FINANCIAL DISTRESS TERHADAP AUDIT DELAY (Studi Empiris Pada Perusahaan Sektor Perdagangan, Jasa dan Investasi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2022): Studi Empiris pada Perusahaan Sektor Perdagangan, Jasa dan Investasi yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022 - Rahayu, Ni Komang Natia; Erni Sulindawati, Ni Luh Gede (Vokasi : Jurnal Riset Akuntansi, 2024)
The purpose of this study is to determine empirically related to the effect of the size of public accounting firms, audit fees, and financial distress on audit delays in companies in the trade, services and investment sectors that have been listed on the Indonesia Stock Exchange in 2020-2022. The quantitative approach is this type of research using secondary data sources obtained from the company's financial statements through the official IDX website. Sampling using purposive sampling techniques so that samples that meet the criteria amounted to 127 companies. The analysis method was carried out by descriptive statistical tests, structural equation modeling-partial least square (SEM-PLS) and hypothesis testing (bootstrapping) using the Smart PLS application version 3.0. The results obtained from this study include (1) the size of KAP has a negative and significant effect on audit delay, (2) audit fees have a negative and significant effect on audit delay, and (3) financial distress has no effect on audit delay.